Potential as biogas energy and organic fertilizer: a mixture of rice husks and cow dung on full scale anaerobic digestion - Matin, Hashfi Hawali Abdul; Syafrudin, Syafrudin; Suherman, Suherman; Budiyono, Budiyono; Syaichurrozi, Iqbal (Institute of Advanced Engineering and Science, 2025)
Rice husk is a biomass that can potentially be converted into biogas energy. In this research, a study was carried out regarding the effect of alkaline pretreatment and then a study related to the potential for developing biogas from rice husks in Indonesia and a study related to the potential utilization of biogas by-products in the form of slurry as solid organic fertilizer. So, the main objective is to determine the effect of alkaline pretreatment of rice husks on the potential development of rice husks as raw material for biogas production on a full-scale anaerobic digestion (AD). Research related to the effect of alkaline pretreatment using 3% NaOH by immersion in the substrate for 24 hours was carried out on a lab scale. The variable TS is set at 27%, C/N ratio is 35, uses a 2-liter digester, and measurements are carried out every other day for 60 days. Furthermore, the up-scale was carried out with an AD fixed dome model with a volume of 6 m3. In this study, it was found that pre-treatment with 3% NaOH increased biogas productivity by 1.6 times higher. The potential for rice husk to be converted into biogas energy can reach 3.5 million liters of biogas by 2022. The by-product of biogas in the form of slurry also has the potential to be used as solid organic fertilizer directly. Parameter tests that have been carried out show that the slurry in biogas from rice husks that have gone through a 60-day AD fermentation process complies with the Indonesian National Standard (SNI) 7763:2018 concerning solid organic fertilizers.